Efficacy and safety of drug-eluting stents versus bare-metal stents in symptomatic intracranial and vertebral artery stenosis: a meta-analysis - Yidan Zhang; Wenbin Li; Lei Zhang (Frontiers in Neurology)
ObjectivesThis study aims to present the first comprehensive meta-analysis assessing the effectiveness and safety of drug-eluting stents (DES) versus bare-metal stents (BMS) in treating intracranial and vertebral artery stenosis.MethodsA comprehensive examination was undertaken to compare the effectiveness and safety of DES and BMS in individuals experiencing symptomatic stenosis in the intracranial and vertebral arteries through an in-depth analysis of clinical research. We conducted an extensive search across multiple databases including PubMed, Embase, Web of Science, and the Cochrane Library up to September 2024. The emphasis of our investigation was on various outcomes including rates of in-stent restenosis, symptomatic occurrences of in-stent restenosis, incidence of stroke, procedural success, mortality rates, complications associated with the procedure, and any adverse events.ResultsOur analysis included 12 studies with a total of 1,243 patients (562 in the DES group and 681 in the BMS group). The findings demonstrated a significantly lower rate of in-stent restenosis in the DES group for both intracranial [odds ratio (OR): 0.23; 95% confidence interval (CI): 0.13 to 0.41; p < 0.00001] and vertebral artery stenosis (OR: 0.38; 95% CI: 0.20 to 0.72; p = 0.003) compared to the BMS group. Additionally, the DES group showed a significantly reduced rate of postoperative strokes in vertebral artery stenosis cases (OR: 0.38; 95% CI: 0.16 to 0.90; p = 0.03), with no significant differences noted in the intracranial artery stenosis comparison (OR: 0.63; 95% CI: 0.20 to 1.95; p = 0.42). The study also revealed no significant disparities in symptomatic in-stent restenosis, procedural success, mortality, adverse effects, and perioperative complications between the two groups across the conditions studied.ConclusionThe comparison indicates that DES significantly reduces the risk of in-stent restenosis and postoperative strokes in patients with vertebral artery stenosis, compared to BMS. For both intracranial and vertebral artery stenosis, DES and BMS exhibit comparable safety profiles.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/display_record.php?RecordID=439967.